Revolutionising pesticide detection: a high-sensitivity electrochemical sensor with CdS/g-C3N4/MWCNTs for paraquat monitoring - Mohamad Idris Bin Saidin, Illyas bin Md Isa, Mohamad Saufi bin Rosmi, Norhayati binti Hashim, Mohamad Syahrizal bin Ahmad, Siti Nur Akmar binti Mohd Yazid, Aireen Aina Binti Bahari (Tanjung Malim, 2024)
Revolutionising pesticide detection: a high-sensitivity electrochemical sensor with CdS/g-C3N4/MWCNTs for paraquat monitoring by Mohamad Idris Bin Saidin, Illyas bin Md Isa, Mohamad Saufi bin Rosmi, Norhayati binti Hashim, Mohamad Syahrizal bin Ahmad, Siti Nur Akmar binti Mohd Yazid, Aireen Aina Binti Bahari